Endophyte Infected Tall Fescue: Plant Symbiosis to Animal Toxicosis - Ferguson, Taylor D.; Vanzant, Eric S.; McLeod, Kyle R. (Frontiers in Veterinary Science, 2021)
Endophyte-infected fescue is a major cool season forage used for livestock production in the United States and through other areas of the world. A unique aspect of this forage resource is the symbiotic relationship with an endophytic fungus (Epichloё coenophiala) that has detrimental impact on herbivores due to toxic ergot alkaloids. Research over the past 50 years has unveiled details regarding this symbiotic relationship. This review focuses on the origin of tall fescue in the United States and the consequences of its wide-spread utilization as a livestock forage, along with the discovery and toxicodynamics of ergot alkaloids produced by E. coenophiala. The majority of past ergot alkaloid research has focused on observing phenotypic changes that occur in livestock affected by ergot alkaloids, but recent investigation of the metabolome, transcriptome, and proteome have shown that fescue toxicity-related illnesses are much more complex than previous research suggests.